Representasi Sarkasme dalam Komunikasi Digital: Analisis Pragmatik pada Kolom Komentar TikTok @Chintyamelsan - Ardiyanti Wardana; Andi Saadillah; Eko Putra; La Alu (Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to identify the forms and analyze the functions of sarcasm in the TikTok comment section of the @Chintyamelsan account using a stylistic and pragmatic approach. The study employs a descriptive-interpretive qualitative method, with data consisting of comments containing sarcasm, collected through non-participant observation and documentation between January and December 2024. The data were analyzed using the interactive model by Miles, Huberman, and Saldaña through the stages of reduction, categorization, interpretation, and drawing conclusions. Theoretically, the analysis draws on Keraf’s stylistics theory, Grice’s conversational implicatures, and Searle’s speech acts. The research findings indicate that sarcasm manifests in the form of insults, mockery, indirect sarcasm, hyperbole, and derogatory comparisons, with a predominance of insults based on physical and social attributes. From a pragmatic perspective, sarcasm operates through violations of the maxims of quality and relevance, thereby generating an implicit meaning of negative evaluation. Furthermore, sarcasm is dominated by expressive speech acts and functions as an indirect directive to convey criticism. These findings indicate that sarcasm in digital communication serves not only as a stylistic device but also as a social strategy to belittle and discredit individuals. This study contributes to the development of linguistic research through the integration of stylistic and pragmatic approaches in the analysis of social media language.